PEMANFAATAN ANALISA MATEMATIS DALAM PENYELESAIAN PERMASALAHAN FIKIH - Mutmainnah Mutmainnah (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
This article intends to clarify the role of mathematics in the study of fiqh. Apart from inheritance, the study of astronomy is in direct contact with the improvement of fiqh worship, especially the prayers and fasting of Ramadan. However, its role is a supporter that must be strengthened by the main fiqh sources. This is evident in the process of determining the initial time of the five daily prayers. Through literature explanations relating to the coordinate system of celestial bodies, a celestial spherical triangle can be formulated in sin, cos and tangent which can be converted into measurements of praying time on earth. So it is not wrong if falak also knows the science of Hisab